PERSEPSI WISATAWAN TERHADAP FASILITAS WISATA RELIGI MASJID ISTIQLAL DI JAKARTA - Prili Diana Rosa; Gagih Pradini (Media Bina Ilmiah, 2023)
The development of the tourism industry can be influenced by tourist satisfaction with the facilities available at a tourist attraction. The purpose of this study was to determine tourists' perceptions of religious tourism facilities at the Istiqlal Mosque in Jakarta. The research method used is a mixture by linking three variables, namely physical conditions, cleanliness, and comfort of tourist facilities. Data collection techniques were carried out by interviews, observation, questionnaires, and documentation studies. The collected data were then analyzed descriptively and also used SWOT analysis. The results showed that tourists' perceptions of tourist facilities based on physical conditions around 50% were classified in the very adequate category, based on cleanliness as much as 66.67% were classified in the very adequate category, and based on comfort 83.33% were classified in the very adequate category.